Towards Excited Radiative Transitions in Charmonium - O'HARA, CIAN (Trinity College Dublin. School of Mathematics. Discipline of Pure & Applied Mathematics, 2019)
In this thesis lattice QCD is utilised to investigate the spectrum of charmonium and charmed mesons with the aim of working towards investigating radiative transitions between excited states in the charmonium spectrum. Results are presented from a dynamical Nf = 2 + 1 lattice QCD study of the excited spectrum of Ds and D mesons at a single lattice spacing with pion mass Mπ = 236 MeV, which has been published in reference [1]. A robust determination of the highly excited spectrum of states, up to spin J = 4, was achieved with the use of distillation and the variational method. A comparison with earlier studies of the spectra on lattices with heavier light quarks was performed and the spectrum was found to have little dependence on the light quark mass. Results from an investigation into radiative transitions in the charmonium spectrum are also presented. A number of transitions are investigated and compared to experiment where possible. Three point correlation functions with a vector current insertion are calculated for a range of source and sink momenta allowing for the extraction of radiative formfactors for a wide range of Q2 values. In particular, the transition J/ψ → ηcγ was investigated and found to be consistent with previous lattice results.
APPROVED
Keywords: Charmonium; Radiative Transitions; Lattice Spectroscopy; Lattice QCD